Pengembangan Sumber Daya Aparatur Pada Kantor Balai Pemantapan Kawasan Hutan (BPKH) Wilayah XV Provinsi Gorontalo - Armanto Amrin (CV. Dalle’ Deceng Abeeayla, 2024)
This research aims to find out and analyze how the implementation of apparatus resource development at the Region XV Forest Area Stabilization Center improves performance. To determine the positive impact of developing apparatus resources and the factors inhibiting the development of apparatus resources at the Office of the Forest Area Stabilization Center for Region XV, Gorontalo Province. This research uses a qualitative method with a phenomenological approach and data collection techniques using observation, interviews and documentation. The results of the research show that the Implementation of Apparatus Resource Development at the Forest Area Stabilization Center for Region The positive impact of developing apparatus resources at the Office of the Forest Area Stabilization Center for Region (1) inadequate work experience of the apparatus; (2) ineffective human resource development; and (3) placement of apparatus work positions that do not match competency.